Arcaro’s Total Quality Management Principles As A Strategic Approach To Enhancing Educational Service Quality In Indonesia - Rahmadi; Muhsinin; Aslamiah; Celiya Cinantya (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Total Quality Management (TQM) has developed into a key managerial approach for enhancing educational quality. Arcaro introduced five core TQM principles in the educational context customer focus, total involvement, measurement, continuous improvement, and commitment which serve as a comprehensive framework for organizational improvement. This study examines the applicability of Arcaro’s TQM principles as a strategic approach for strengthening educational service quality in response to 21st-century demands. This research adopts a library study design by reviewing 35 literature sources, including national and international journal articles, authoritative books, and previous empirical studies on TQM implementation in education. The sources were selected based on relevance to TQM theory, publication within the last ten years (except foundational works), and methodological rigor. Data were analyzed through qualitative content analysis, involving categorization, comparison, and synthesis of key concepts across the selected literature. The findings show that Arcaro’s TQM principles align strongly with contemporary national and global quality standards by emphasizing stakeholder satisfaction, collaborative participation, evidence-based evaluation, continuous refinement, and leadership commitment. These principles consistently emerge as a strategic foundation for improving educational service quality, although implementation may be constrained by factors such as limited institutional resources, bureaucratic structures, and resistance to organizational change. Theoretically, this study contributes by reaffirming Arcaro’s TQM as a relevant framework for modern educational quality management. Practically, it offers guidance for schools and higher education institutions seeking structured strategies to enhance service quality through stakeholder engagement, data-driven practices, and continuous improvement mechanisms.